2010
DOI: 10.1007/s00775-010-0645-y
|View full text |Cite
|
Sign up to set email alerts
|

Nickel superoxide dismutase: structural and functional roles of Cys2 and Cys6

Abstract: Nickel superoxide dismutase (NiSOD) is unique among the family of SOD enzymes in that it coordinates cysteine residues (Cys2 and Cys6) to the redox-active metal center and exhibits a hexameric quaternary structure. To assess the role of the Cys residues with respect to the activity of NiSOD, mutations of Cys2 and Cys6 to serine (C2S-, C6S-, and C2S/C6S-NiSOD) were carried out. The resulting mutants do not catalyze the disproportionation of superoxide, but retain the hexameric structure found for wild-type (WT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
67
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 59 publications
9
67
0
1
Order By: Relevance
“…Such high-spin Ni(II) centers have also been observed in Cys-to-Ser mutants of NiSOD, which are catalytically inactive. (14, 27) The formation of a high-spin six-coordinate complex for the disordered “Ni-hook” domain may also sterically prevent folding into the “Ni-hook” structure that features a His1 imidazole-Glu17 H-bond, a possible explanation for why exogenous imidazole does not complement the loss of the His1 imidazole ligand.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Such high-spin Ni(II) centers have also been observed in Cys-to-Ser mutants of NiSOD, which are catalytically inactive. (14, 27) The formation of a high-spin six-coordinate complex for the disordered “Ni-hook” domain may also sterically prevent folding into the “Ni-hook” structure that features a His1 imidazole-Glu17 H-bond, a possible explanation for why exogenous imidazole does not complement the loss of the His1 imidazole ligand.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative analyses of the Ni K-edge EXAFS spectra from a number of NiSOD samples have shown that binding the His1 side chain results in two resolved features in the Fourier-transform (FT)-EXAFS spectrum that arise from the first-coordination sphere ligands, whereas in the absence of the apical ligand, only one broad feature is observed. (14) This presumably arises from the presence of a unique longer Ni-N vector in samples with an apical imidazole ligand. This observation is true of oxidized vs. reduced WT-NiSOD, and for H1A-NiSOD, which has only one broad feature in the FT-EXAFS spectrum.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations